The multifunctional Ca2+/calmodulin-dependent kinase II regulates vascular smooth muscle migration through matrix metalloproteinase 9 - Scott, Jason A.; Backs, Johannes (American journal of physiology. Heart and circulatory physiology, 2012)
The multifunctional CaMKII has been implicated in vascular smooth muscle cell (VSMC) migration, but little is known regarding its downstream targets that mediate migration. Here, we examined whether CaMKII regulates migration through modulation of matrix metalloproteinase 9 (MMP9). Using CaMKIIδ−/− mice as a model system, we evaluated migration and MMP9 regulation in vitro and in vivo. After ligation of the common carotid artery, CaMKII was activated in the neointima as determined by oxidation and autophosphorylation. We found that MMP9 was robustly expressed in the neointima and adventitia of carotid-ligated wild-type (WT) mice but was barely detectable in CaMKIIδ−/− mice. The perimeter of the external elastic lamina, a correlate of migration-related outward remodeling, was increased in WT but not in CaMKIIδ−/− mice. Migration induced by serum, platelet-derived growth factor, and tumor necrosis factor-α (TNF-α) was significantly decreased in CaMKIIδ−/− as compared with WT VSMCs, but migration was rescued with adenoviral overexpression of MMP9 in CaMKIIδ−/− VSMCs. Likewise, overexpression of CaMKIIδ in CaMKIIδ−/− VSMCs increased migration, whereas an oxidation-resistant mutant of CaMKIIδ did not. TNF-α strongly induced CaMKII oxidation and autophosphorylation as well as MMP9 activity, mRNA, and protein levels in WT, but not in CaMKIIδ−/− VSMC. Surprisingly, TNF-α strongly induced MMP9 promoter activity in WT and CaMKIIδ−/− VSMC. However, the MMP9 mRNA stability was significantly decreased in CaMKIIδ−/− VSMC. Our data demonstrate that CaMKII promotes VSMC migration through posttranscriptional regulation of MMP9 and suggest that CaMKII effects on MMP9 expression may be a therapeutic pathway in vascular injury.
Im Titel ist 2+ hochgestellt
Published online 15 May 2012
Gesehen am 20.06.2018